Pola Distribusi Mikroba dan Pengaruhnya Terhadap Pembenihan Larva Udang Vanamei Di Hatchery Pantai Ketang Lampung - Sarwoko, Jonathan Puji; Sumardi; Tugiyono; Nugroho Susanto, Gregorius; Irawan, Bambang (ECOTAS, 2024)
Abstract: The microbial distribution pattern or dispersion of microbes in a water environment was the primary focus of this research. The study aimed to analyze the total density of Vibrio sp., coliform, and plankton in seawater, as well as the relationship between microbes and the hatching of vanamei shrimp larvae. The research was conducted from April to August 2022 at Pantai Ketang, Kalianda, Lampung, in the Microbiology and Zoology laboratory of the Faculty of Mathematics and Natural Sciences, Lampung University. The research employed an exploratory survey method, including the calculation of total Vibrio, coliform, plankton, and survival rates. Data analysis was carried out using analysis of variance, followed by the Duncan test (? = 0.05) for identifying significant differences among groups. Additionally, the microbial relationship was analyzed using Pearson correlation (? = 0.05). The results revealed that the highest Vibrio density occurred in May (3 CFU/ml) and in larval shrimp rearing water (M) (5 CFU/ml). Coliform density was less than < 3 MPN/100ml, and the highest plankton density was observed in August (2×102 ind/L) and in high tide seawater (P) (1×104 ind/L). However, there was a very low correlation between microbial density and the survival rate of vanamei shrimp larvae.